Porous Materials - Bruce, D; O'Hare, D; Walton, R (2010)
In the past few decades, the increasingly routine use of advanced structural probes for studying the structure and dynamics of the solid state has led to some dramatic developments in the field of porous solids. These materials are fundamental in a diverse range of applications, such as shape-selective catalysts for energy-efficient organic transformations, new media for pollutant removal, and gas storage materials for energy technologies. Porosity in inorganic materials may range from the nano-scale to the macro-scale, and the drive towards particular properties remains the goal in this fast-developing area of research. Covering some of the key families of inorganic solids that are currently being studied, Porous Materials discusses: Metal Organic Frameworks Materials Mesoporous Silicates Ordered Porous Crystalline Transition Metal Oxides Recent Developments in Templated Porous Carbon Materials Synthetic Silicate Zeolites: Diverse Materials Accessible Through Geoinspiration Additional volumes in the Inorganic Materials Series: Low-Dimensional Solids|Molecular Materials|Functional Oxides|Energy Materials. © 2011 John Wiley and Sons, Ltd.